Word into image. Screenwriter, Robert Towne - Towne, Robert; American Film Foundation (Santa Monica, CA : The Foundation, 1984)
An interview with screenwriter Robert Towne. He discusses his work and philosophy, stating that he believes that the writer has more control over his art than the director. Towne's anecdotes show how he often finds his material in unorthodox sources. Including clips from the screenwriter's films.
Title from data sheet.
Subtitle: Writers on screenwriting.
Originally shown on public television.
Intended audience: Adults.
Issued as VHS 1/2 in.
Keywords: Towne, Robert; Screenwriters -- United States -- Interviews; Motion picture authorship